Quantitative analysis of questionnaires : techniques to explore structures and relationships - Humble, Steve (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Bringing together the techniques required to analyse questionnaires, this book is the ideal companion for non-mathematical students with no prior knowledge of quantitative methods. Using rich examples from a range of settings, this book analyses basic principles, provides hands on data analysis with data sets and both SPSS and Stata packages and explores how to articulate the calculations and theory around the statistical techniques. This is the ideal introductory textbook for any student looking to begin and expand their knowledge on how to analyse questionnaires and help improve statistical knowledge and learning as well as interpretation"--
Includes bibliographical references and index.
Keywords: SPSS (Computer file); Stata; Statistics -- Computer programs; Social sciences -- Research -- Statistical methods; Quantitative research -- Statistical methods